Possibilities to use textile cord waste from used tires for concrete - Malaiškienė, Jurgita; Nagrockienė, Džigita; Skripkiūnas, Gintautas (Journal of Environmental Engineering and Landscape Management, 2015)
The goal of the study was to determine the effect of waste tire cord yarn with attached rubber particles on the properties of concrete made of different types of cement (Portland cement without additives – CEM I, Portland cement with limestone additive – CEM II). The filament waste (added at 0%, 2%, 4%, 6%, 8%, and 10% of the amount of fine aggregate) is water absorbing textile fibre additive with rubber particles, therefore a bigger amount of water is required to prepare the concrete mixture. With waste additive, the density and compressive strength of concrete reduces, but water absorption increases. The forecasted freeze-thaw resistance of concrete with cement type CEM I and recycled tire cord increases and slightly reduces when cement type CEM II is used, however retains similar resistance in about 1000 freeze-thaw cycles. The coefficient of thermal conductivity decreases approx. 35%, when 10% of recycled tire textile cord is added to concrete mixture.